RELATION OF THE STRUCTURE AND DIVERSITY OF VEGETATION WITH LANDSCAPE METRIC IN THE VANGUARDIA FOREST RESERVE, VILLAVICENCIO, COLOMBIA - Velosa Caicedo, Rodrigo Isaac; Duque, Veronica; Herrera, Francois (Floresta, 2022)
Some human activities have caused a decrease in coverage in the Vanguardia Reserve and changes in the diversity and structure of the vegetation. The objective of the study was to compare the diversity and structure of vegetation, relating habitat variables with landscape metrics. Vegetation was sampled in five sectors; in each sector 3 plots of 50 x 2 m were established, except in Ocarros where 4 plots were evaluated. In each plot, all trees and shrubs with diameter at breast high DBH ≥ 1.0 cm were censored. An ANOVA was performed to compare the structure and diversity between plots. A floristic similarity dendrogram was developed using the Bray-Curtis index. Pearson correlations were calculated between habitat variables and landscape metrics using PAST. No significant differences in diversity and abundance were found between the compared plots. DBH averages and coverage showed statistical differences between some plots. The richness of trees, shrubs and total abundance was positively correlated with the distance to the roadways. The diversity was negatively correlated with the distance to the mature forest fragment. The differences in coverage and DAP suggest that the reserve is facing different degrees of disturbance, causing variation in ecological attributes. The positive correlations between some vegetation variables and landscape metrics indicate that the roads influence the structure and diversity of the vegetation